Impact of memory T cells on SARS-CoV-2 vaccine response in hematopoietic stem cell transplant - Jennifer VanOudenhove; Yuxin Liu; Raman Nelakanti; Dongjoo Kim; Emma Busarello; Natalia Tijaro Ovalle; Zhihong Qi; Padmavathi Mamillapalli; Alexa Siddon; Zhiliang Bai; Alfredo Axtmayer; Cheryl Corso; et al. (PLoS ONE, 2025)
During the COVID-19 pandemic, hematopoietic stem cell transplant (HSCT) recipients had elevated mortality rates from SARS-CoV-2 infection, ranging between 10–40%. SARS-CoV-2 mRNA vaccines are important tools in preventing severe disease, yet their efficacy post-transplant remains unclear, especially in patients subjected to myeloablative chemotherapy and immunosuppression. We evaluated humoral and adaptive immune responses to the SARS-CoV-2 mRNA vaccination series in 42 HSCT recipients and 5 healthy controls. Post-vaccination responses were assessed by anti-spike IgG and nucleocapsid levels, and antigen specific T cell activity. Immune profiling was performed using clinical flow and mass cytometry. Patients were selected based on humoral and cellular responses for single-cell RNA with TCR and BCR sequencing. Our studies revealed defects in memory T cells that correlated with an absence of cellular response despite nearly universal humoral response. Several patients with a robust antibody response developed COVID-19 infection, but none developed severe disease or died from the infection.